2015
DOI: 10.1111/rec.12289
|View full text |Cite
|
Sign up to set email alerts
|

The use of remote sensing to develop a site history for restoration planning in an arid landscape

Abstract: Developing a site history and ecological site description is one of the critical steps in restoration planning for arid landscapes. This study focuses on Umm Nigga, Northeast of Kuwait, which was damaged by various human activities. The northern portion of Umm Nigga falls within the boundaries of the demilitarized zone (DMZ) adjacent to Iraq, and was fenced off to restrict public access since 1994. The central objective of this project was to use remote sensing, field assessment, and Geographical Information S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…Remotely sensed imagery is becoming a common tool for reconstructing a site's history and detecting changes in vegetation cover (Zweig & Newman 2015;Abdullah et al 2016). Several researchers agree that remote sensing (RS) can help generate the necessary information to study the distribution of vegetation cover (Shuman & Ambrose 2003;Muthumanickam et al 2011;Im et al 2012;Peng et al 2012;Harris et al 2014) and monitor desertification (Diouf & Lambin 2001;Mollot & Bilby 2008;Malmstrom et al 2009) in arid and semi-arid lands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remotely sensed imagery is becoming a common tool for reconstructing a site's history and detecting changes in vegetation cover (Zweig & Newman 2015;Abdullah et al 2016). Several researchers agree that remote sensing (RS) can help generate the necessary information to study the distribution of vegetation cover (Shuman & Ambrose 2003;Muthumanickam et al 2011;Im et al 2012;Peng et al 2012;Harris et al 2014) and monitor desertification (Diouf & Lambin 2001;Mollot & Bilby 2008;Malmstrom et al 2009) in arid and semi-arid lands.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers agree that remote sensing (RS) can help generate the necessary information to study the distribution of vegetation cover (Shuman & Ambrose 2003;Muthumanickam et al 2011;Im et al 2012;Peng et al 2012;Harris et al 2014) and monitor desertification (Diouf & Lambin 2001;Mollot & Bilby 2008;Malmstrom et al 2009) in arid and semi-arid lands. RS allows researchers to examine dynamic landscape changes (Herold et al 2002;Groom et al 2006;Jia et al 2008;Hadeel et al 2010;Abdullah et al 2016), but the classification of arid land vegetation images can be challenging because of the high reflectance of the soil background, variable mixture of green and senescent grasses, shrubs and herbs, and multiple reflectance from open canopies and bright soils (Laliberte et al 2007). The vegetation of Kuwait is characterized mainly by open dwarf shrubs, perennial herbs and ephemerals, and rare taller shrubs (Halwagy & Halwagy 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Most actions taken by decision-makers focused on solving one part of the system, which may end up declining other parts, leading to failure in managing and restoring ecological systems. It is also important to understand that restoration of disturbed ecosystems is costly, and that one restoration program is not suitable for all locations, it significantly depends on the type and degree of disturbance, and site condition [8] [33] [34].…”
Section: The Complexity Of the Natural Ecosystemmentioning
confidence: 99%
“…Therefore, the social-ecological system is a critical aspect that needs to be addressed in this approach. Previous work showed that human activities were the primary source of disturbance in the State of Kuwait [8]. The degradation of the ecosystem is also influenced by the rapid urbanization processes leading to more loses in the ecosystem services.…”
Section: Anthropogenic Activities: Human Activitiesmentioning
confidence: 99%
See 1 more Smart Citation